Change your words, change your life [compact disc, unabridged] : understanding the power of every word you speak - Meyer, Joyce, 1943- (Hachette Audio, 2012)
Building on the premises of 'Power thoughts and living beyond your emotions', Joyce Meyer examines the tremendous power of words, which are the vehicles that convey thoughts and emotions, and provides a series of guidelines for making sure that talk is constructive, healthy, healing, and used to good results.